2022
DOI: 10.3390/foods11233877
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Gut Microbiota Structure and Function by Two Structurally Different Lemon Pectins

Abstract: Pectins are plant polysaccharides consumed as part of a diet containing fruits and vegetables. Inside the gastrointestinal tract, pectin cannot be metabolized by the mammalian cells but is fermented by the gut microbiota in the colon with the subsequent release of end products including short-chain fatty acids (SCFA). The prebiotic effects of pectin have been previously evaluated but reports are inconsistent, most likely due to differences in the pectin chemical structure which can vary by molecular weight (MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…The higher percentage of arabinose has been linked to an increase of acetate and propionate producers in earlier research (Tomioka et al, 2022). In studies with humans and animals, pectin fermentation leads to formation of acetate over propionate and butyrate (Firrman et al, 2022;Langhout & Schutte, 1996;Larsen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The higher percentage of arabinose has been linked to an increase of acetate and propionate producers in earlier research (Tomioka et al, 2022). In studies with humans and animals, pectin fermentation leads to formation of acetate over propionate and butyrate (Firrman et al, 2022;Langhout & Schutte, 1996;Larsen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown that lemon pectin could increase the level of Lachnospiraceae family in the human gut, but pectin with different esterification degrees and molecular weight had different effects on the intestinal flora ( 100 ). Uncultured_bacterium_f_Lachnospiraceae exhibited potential reduces the activity of fat deposits and metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Following overnight growth, the cultivars were maintained with daily feeding cycles in which the cultivar was provided fresh medium and pancreatic juice. Every 8 h, the volume of the cultivar was reduced to 800 mL, and 200 mL of a 70:30 defined medium: pancreatic juice mixture was added ( 51 , 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial load was determined using quantitative PCR targeting the V3/V4 hypervariable regions of the 16S rRNA gene as described previously ( 52 ). Primers and g block were synthesized by Integrated DNA Technologies (Skokie, IL).…”
Section: Methodsmentioning
confidence: 99%